Design of a fuel oil measuring device for on arduino mega based SPBT tank at Indonesian army unit - Faris Handika Faris; Jeki Saputra Jeki; Maariful Huda Huda; Dekki Widiatmoko Dekki; Kasiyanto Kasiyanto (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Fuel storage in storage tanks (SPBT) generally uses manual methods, causing inaccuracies and inefficiencies. To overcome this problem, this research focuses on developing a microcontroller-based automatic measuring instrument with a PING ultrasonic sensor. Manual methods are often prone to human error, while these automated tools are designed to improve measurement accuracy and efficiency. By using a PING ultrasonic sensor, this tool can measure liquid levels with a higher degree of accuracy, reducing the potential for error. This automated process enables real-time monitoring, with measurement results directly displayed on the monitor or LCD. The use of this method also allows measurements based on cylindrical tank type, increasing operational flexibility. The research results show that this tool is more efficient than manual methods, minimizing errors and increasing information availability. Evaluation of the entire system shows that the desired fuel oil stock monitoring system can provide adequate performance, as well as ensure stock maintenance is maintained properly. However, there is an average error of about 0.11% in the tank volume measurements, which is caused by slight curvature in the tank structure. In conclusion, the use of this technology in SPBT is expected to increase fuel management efficiency, reduce operational costs, and provide information on fuel availability accurately and quickly. Thus, this research makes a significant contribution to the development of more effective storage tank monitoring and management systems